Magnetic microparticles post-synthetically coated by hyaluronic acid as an enhanced carrier for microfluidic bioanalysis - Holubova, Lucie; Knotek, Petr; Palarcik, Jiri; Cadkova, Michaela; Belina, Petr; Vlcek, Milan; Korecka, Lucie; Bilkova, Zuzana (Materials science & engineering. C, Materials for biological applications, 2014)
Iron oxide based particles functionalized by bioactive molecules have been utilized extensively in biotechnology and biomedicine. Despite their already proven advantages, instability under changing reaction conditions, non-specific sorption of biomolecules on the particles' surfaces, and iron oxide leakage from the naked particles can greatly limit their application. As confirmed many times, surface treatment with an appropriate stabilizer helps to minimize these disadvantages. In this work, we describe enhanced post-synthetic surface modification of superparamagnetic microparticles varying in materials and size using hyaluronic acid (HA) in various chain lengths. Scanning electron microscopy, atomic force microscopy, phase analysis light scattering and laser diffraction are the methods used for characterization of HA-coated particles. The zeta potential and thickness of HA-layer of HA-coated Dynabeads M270 Amine were -50 mV and 85 nm, respectively, and of HA-coated p(GMA-MOEAA)-NH2 were -38 mV and 140 nm, respectively. The electrochemical analysis confirmed the zero leakage of magnetic material and no reactivity of particles with hydrogen peroxide. The rate of non-specific sorption of bovine serum albumin was reduced up to 50% of the naked ones. The coating efficiency and suitability of biopolymer-based microparticles for magnetically active microfluidic devices were confirmed.
Keywords: povrchové vlastnosti; magnetismus; Hyaluronic Acid; Chemical Phenomena; železité sloučeniny; Microfluidics; mikroskopie elektronová rastrovací; velikost částic; sérový albumin hovězí; Serum Albumin, Bovine; chemické jevy; Magnetics; Surface Properties; kyselina hyaluronová; Ferric Compounds; Microscopy, Electron, Scanning; Particle Size; mikrofluidika